Paleoceanographic changes during the Albian-Cenomanian in the Tethys and North Atlantic and the onset of the Cretaceous chalk - Giorgioni, Martino; Weissert, Helmut; Bernasconi, Stefano M.; id_orcid:0 000-0001-7672-8856; Hochuli, Peter A.; Keller, Christina E.; Coccioni, Rodolfo; Petrizzo, Maria Rose; Lukeneder, Alexander; Garcia, Therese I. (Global and Planetary Change, 2015)
ISSN:0921-8181